Effect of a telecare-based intervention on stress levels in informal caregivers of older adults: protocol for a randomized controlled trial - Wong, Arkers Kwan Ching; Ng, Nga Ping; Hui, Vivian Chi Ching; Montayre, Jed (Frontiers in Psychiatry, 2023)
Significance: Due to caregiving commitments, caregivers of older adults may not have the time to make use of the onsite community services available to them during the day. With the support of advanced technology, telecare could be a convenient and easily accessible channel for providing individualized caregiving advice to caregivers. Objective: The aim of the study is to describe a research protocol that highlights the development of a telecare-based intervention program for reducing stress levels in informal caregivers of community-dwelling older adults. Methods: It is a randomized controlled trial. The study is supported by two community centers. The study participants will be randomly assigned to either the telecare-based intervention group or the control group. The former will receive a 3-month program comprised of three components: online nurse case management supported by a health and social care team, an online resource center, and a discussion forum. The latter will receive the usual services that provided by the community centers. Data will be collected at two time points – pre-intervention (T1) and post-intervention (T2). The primary outcome is stress levels, while secondary outcomes include self-efficacy, depression levels, quality of life, and caregiving burden. Discussion: Besides taking care of one or more older adults, informal caregivers have to deal with work, chores, and take care of their children. This study will add valuable information to the knowledge gap on whether telecare-based interventions with the support of an integrated health-social team can alleviate the stress levels of informal caregivers of community-dwelling older adults. If successful, policymakers and healthcare professionals should consider incorporating telecare modalities in a primary health setting for informal caregivers to correspond with them, to relieve their caregiving stress and promote a healthy life.